An in-vitro analysis to evaluate the disinfection effectiveness of Cold Atmospheric Pressure (CAP) plasma jet in Enterococcus faecalis infected root canals. Issue 1 (31st December 2023) - Kumar, Pravin; Soundharrajan, P.; Prakash, Ram; Kombade, Sarika Prabhakar; Yadav, Pankaj; Chugh, Ankita; Patnana, Arun Kumar
Abstract: Cold Atmospheric Pressure (CAP) plasma has shown successful antibacterial efficacy in different medical applications which have prompted researchers to explore its possible use in endodontics. The aim of the present study was to comparatively evaluate the disinfection effectiveness of CAP Plasma jet with 5.25% sodium hypochlorite (NaOCl) and Qmix in Enterococcus Faecalis infected root canals at different time intervals (2, 5, and 10 min). 210 single-rooted mandibular premolars were chemomechanically prepared and infected with E. faecalis . The test samples were exposed to CAP Plasma jet, 5.25% NaOCl, and Qmix for 2, 5, and 10 min. The residual bacteria from the root canals if any were collected and evaluated for colony-forming units (CFUs) growth. ANOVA and Tukey's tests were used to evaluate the significant difference between treatment groups. 5.25% NaOCl showed significantly more antibacterial effectiveness (<0.001) when compared with all other test groups except Qmix at 2 and 10 min of exposure time. A minimum contact time of 5 min with 5.25% NaOCl is recommended to get zero bacterial growth in E. faecalis infected root canals. QMix requires a minimum contact time of 10 min to achieve optimal CFUs reduction and CAP plasma jet requires a minimum contact time of 5 min to achieve substantial CFUs reduction.